Empowering Cultural and Civic Literacy through Anti-Bullying Traditional Game-Based Learning in Elementary School - Wuli Oktiningrum; Lutfiatus Zuhroh; Adzimatnur Muslihasari; Dyah Ayu Pramoda Wardhani; Andi Wibowo (Universitas Negeri Malang, 2026)
Abstract: This study develops and evaluates traditional game–based learning media—Ular Tangga and Engklek—integrated with anti-bullying elements and Indonesian cultural diversity content to enhance elementary students’ cultural and civic literacy. Employing the ADDIE development model, the research involved 28 fifth-grade students for field testing and 10 sixth-grade students for small-group trials. Data were collected through expert validation, observations, interviews, tests, and questionnaires. The learning media demonstrated strong validity, with expert scores exceeding 85%. Students’ learning outcomes improved substantially, as reflected in the increase from an average pre-test score of 56.0 to a post-test score of 81.4. The N-Gain value of 0.8183, categorized as high, confirms the effectiveness of the media in strengthening students’ understanding of cultural diversity and bullying prevention. The findings indicate that embedding cultural, civic, and moral values into traditional games offers a formal, culturally responsive instructional approach that promotes cognitive development and positive social behavior in elementary education. Abstrak: Penelitian ini mengembangkan dan mengevaluasi media pembelajaran berbasis permainan tradisional—Ular Tangga dan Engklek—yang diintegrasikan dengan unsur-unsur anti-bullying dan konten keragaman budaya Indonesia guna meningkatkan literasi budaya dan kewarganegaraan siswa sekolah dasar. Dengan menggunakan model pengembangan ADDIE, penelitian ini melibatkan 28 siswa kelas lima untuk uji lapangan dan 10 siswa kelas enam untuk uji coba kelompok kecil. Data dikumpulkan melalui validasi ahli, observasi, wawancara, tes, dan kuesioner. Media pembelajaran tersebut menunjukkan validitas yang kuat, dengan skor penilaian ahli melebihi 85%. Hasil belajar siswa meningkat secara signifikan, sebagaimana tercermin dari kenaikan skor rata-rata pra-tes sebesar 56,0 menjadi skor pasca-tes sebesar 81,4. Nilai N-Gain sebesar 0,8183, yang dikategorikan sebagai tinggi, menegaskan keefektifan media tersebut dalam memperkuat pemahaman siswa tentang keragaman budaya dan pencegahan perundungan. Temuan ini menunjukkan bahwa pengintegrasian nilai-nilai budaya, kewarganegaraan, dan moral ke dalam permainan tradisional menawarkan pendekatan pembelajaran formal yang responsif secara budaya, yang mendorong perkembangan kognitif dan perilaku sosial yang positif dalam pendidikan dasar.